Immunology (Philadelphia : Wolters Kluwer/Lippincott Williams & Wilkins, 2008)
"Concise review of immunology to be used by resident medical student s"--Provided by publisher.
The need for self recognition -- Antigens and receptors -- Barriers to infection -- Cells of the innate immune system -- Innate immune func tion -- Molecules of adaptive immunity -- Cells and organs -- Generatio n of immune diversity: lymphocyte antigen receptors -- Lymphocyte devel opment -- Lymphocyte activation -- Lymphocyte function -- Regulation of adaptive responses -- The well patient: how innate and adaptive immune responses maintain health -- Hypersensitivity reactions -- Immune defi ciency -- Autoimmunity -- Transplantation -- Immune pharmacotherapy -- Tumor immunity -- Measurement of immune function.
Includes index.
Keywords: Immune System -- physiology; Immunity -- physiology; Outlines